2016
DOI: 10.1159/000446024
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Loci Associated with the Plasma Triglyceride Response to an Omega-3 Fatty Acid Supplementation

Abstract: Background: A recent genome-wide association study (GWAS) by our group identified 13 loci associated with the plasma triglyceride (TG) response to omega-3 (n-3) fatty acid (FA) supplementation. This study aimed to test whether single-nucleotide polymorphisms (SNPs) within the IQCJ, NXPH1, PHF17 and MYB genes are associated with the plasma TG response to an n-3 FA supplementation. Methods: A total of 208 subjects followed a 6-week n-3 FA supplementation of 5 g/day of fish oil (1.9-2.2 g of eicosapentaenoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…Studies have shown that DHA supplementation in the maternal diet may have a favorable impact on the development of the infant's immune system and the risk of allergic or atopic diseases early in life (10). Recent studies also have identified polymorphisms in several genes that could partly explain the large interindividual variability observed in plasma TG concentrations in response to EPA plus DHA supplementation (11).…”
Section: Recent Researchmentioning
confidence: 99%
“…Studies have shown that DHA supplementation in the maternal diet may have a favorable impact on the development of the infant's immune system and the risk of allergic or atopic diseases early in life (10). Recent studies also have identified polymorphisms in several genes that could partly explain the large interindividual variability observed in plasma TG concentrations in response to EPA plus DHA supplementation (11).…”
Section: Recent Researchmentioning
confidence: 99%
“…In our previous study, these SNPs were also found to exert significant gene-diet interactions modulating plasma TG levels [11]. These results therefore indicate that an individual’s genotype may possibly affect gene expression of IQCJ through the alteration of RNA splicing.…”
Section: Discussionmentioning
confidence: 67%
“…We increased the density of markers around GWAS-associated SNPs in the IQCJ , NXPH1 , PHF17 and MYB genes to further verify whether they are associated with plasma TG levels following ω-3 FA supplementation [11]. We found several effects of genotype and gene-diet interactions on plasma TG levels [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations